Stroke Hemorrhagic et Causa Ruptur Aneurysma Anterior Communicating Artery: Case Report - Meilani, Ni Komang Putri; Kamelia, Luh Putu Lina; Permasutha, Made Bayu; Puspitayanti, Ni Putu Leony; Soeka, Luh Made Anindita Adristi (Jurnal Biologi Tropis, 2025)
Bleeding in the brain is life-threatening. Two types of bleeding are subarachnoid hemorrhage (SAH) and intraventricular hemorrhage (IVH). SAH is defined as bleeding that occurs in the subarachnoid space, which is the space between the arachnoid membrane and the pia mater. Meanwhile, IVH is bleeding that occurs within the brain's ventricular system, which is a cavity containing cerebrospinal fluid (CSF). The incidence of SAH is quite high, reaching 8.09 million cases out of all stroke cases. Meanwhile, IVH only accounts for 0.31% of total stroke cases. The purpose of this study is to document medical cases as a form of the latest clinical knowledge. The method used is qualitative with a case study design to analyze the management of hemorrhagic stroke patients at the RSUD Buleleng. The patient underwent a neurological physical examination in the form of a meningeal sign examination, which showed positive neck stiffness, Kernig's sign (-), and Brudzinski's sign I-IV (-). Eye examination revealed that both pupils were 3 mm in size, with light reflexes +/+. The patient did not exhibit any weakness or paralysis on one side of the body. Based on clinical symptoms and findings from radiological examinations and DSA, the patient was diagnosed with Hemorrhagic Stroke + Intraventricular Hemorrhage due to rupture of the anterior communicating artery aneurysm segment A1 with daughter SAC. The patient was administered Loading Normal Saline 0.9% 18 tpm, Oxygen 3 lpm, loading Mannitol 200 mL followed by 100 mL 6 times tapering off, Citicoline 2x250 mg intravenously, Omeprazole 2x40 mg intravenously, Painless 2x400 mg, and Dexamethasone injection 2x1 ampoule. as initial treatment.